Children and structured holiday camping: Processes and perceived outcomes. (July 2020) - Tong, Yixuan; Wu, Mao-Ying; Pearce, Philip L.; Zhai, Junqing; Shen, Haili
Abstract: Holiday camping and time spent in outdoor environments are critical childhood experiences. This study aims to identify the outcomes and processes underlying children's experiences of holiday camping. The researchers use the contextual model of learning as the theoretical background underpinning the study. Chinese children who left their families and participated in structured camping trips formed as the research respondents. Several child-centred research methods, including participant observation, focus group discussions, and interviews based on elicited drawings, were employed to study the children's construction of their experiences. Children mainly reported positive camping outcomes, including enhanced interpersonal skills, improved self-awareness, general knowledge and skills, and positive emotions. Negative outcomes including feelings of anxiety and boredom were also occasionally observed. The ongoing interplay of personal, social, and physical contexts works together to generate these camping outcomes. Practical and theoretical implications are offered to enhance positive outcomes and reduce negative ones when children go camping. Highlights: Outcomes and processes of Chinese children's holiday camping are explored. Multi child-centred qualitative methods are adopted. Both children's positive and negative camping outcomes are discussed. The contextual model of learning is used to examine how outcomes are generated. The interactions of personal, social, and physical contexts generate outcomes.